Overview of the application of active - Nishitani, Akira (Earthquake engineering & structural dynamics.)
Perhaps one of the most significant technological innovations in the structural engineering field is the practical application of active and semiactive control to civil structures. A number of structures integrating active, hybrid, and semiactive response control technologies have been constructed in Japan. Most of them are building structures. This paper provides an overview of those building structures, focusing mainly on the types of buildings that are controlled, and on the types of control devices that are implemented. Future directions of structural engineering are also discussed.